Non-volant small mammals (Rodentia and Didelphimorphia) diversity in an isolated area of the Serra da Mantiqueira, Minas Gerais state, Brazil - Faria, Michel Barros; Lanes, Rayque de Oliveira; Bonvicino, Cibele Rodrigues (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
The southeastern Atlantic Forest of the Zona da Mata Mineira is located in the extreme north of Minas Gerais state, Brazil. The Serra da Mantiqueira, is a mountainous region with a high diversity of small non-volant mammal species, several of which are rare species or endemic lineages. The presence of cryptic species in small mammals makes the karyotype an excellent tool for identification and detection of new lineages. We analyzed the karyotype of 14 species: 11 rodents – Abrawayaomys ruschii, Akodon cursor, Blarinomys breviceps, Delomys sublineatus, Juliomys ossitenuis, Oligoryzomys nigripes, Oligoryzomys flavescens, Oxymycterus dasytrichus, Rhipidomys tribei, Sooretamys angouya, and Thaptomys nigrita; and three marsupials – Monodelphis scalops, Philander quica, and Marmosops incanus. We described for the first time the fundamental autosomal number and the morphology of sex chromosomes of Abrawayaomys ruschii, a rare sigmodontine species, and described a new karyotype for Blarinomys. The revision of published karyotypes of the species herein studied enabled the expansion of the geographic distribution of Oligoryzomys nigripes and Delomys sublineatus.
Keywords: Rodents; Marsupials; Chromosome complement; Geographic distribution